The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1371/journal.pone.0077313
|View full text |Cite
|
Sign up to set email alerts
|

Does the Fat Tailed Damara Ovine Breed Have a Distinct Lipid Metabolism Leading to a High Concentration of Branched Chain Fatty Acids in Tissues?

Abstract: Fat tailed sheep breeds are known for their adaptation to nutritional stress, among other harsh production conditions. Damara sheep, native to Southern Africa, have recently been exported to other areas of the world, particularly Australia, aiming to produce lamb in semi-arid regions. Damaras have a unique hanging fat tail, a fat depot able to be mobilized under nutritional stress. In this article we perform an in-depth characterization of the fatty acid profiles of the fat tail in underfed and control Damara … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 27 publications
(28 reference statements)
3
38
0
1
Order By: Relevance
“…Previous studies with the same animal groups suggest that the Damara breed has a unique lipid metabolism, mostly due to the putative contribution of the fat tail as supplier of odd and branched-chain fatty acids (BCFA) to the muscle40. However, it is also suggested that this tolerance to feed restriction could also be due to some kind of peculiarities in rumen activity40. Specifically, if the Damara breed has some digestive adaptation that can increase the efficiency of fibre digestion, the acetate-propionate ratio will be affected4041.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with the same animal groups suggest that the Damara breed has a unique lipid metabolism, mostly due to the putative contribution of the fat tail as supplier of odd and branched-chain fatty acids (BCFA) to the muscle40. However, it is also suggested that this tolerance to feed restriction could also be due to some kind of peculiarities in rumen activity40. Specifically, if the Damara breed has some digestive adaptation that can increase the efficiency of fibre digestion, the acetate-propionate ratio will be affected4041.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also suggested that this tolerance to feed restriction could also be due to some kind of peculiarities in rumen activity40. Specifically, if the Damara breed has some digestive adaptation that can increase the efficiency of fibre digestion, the acetate-propionate ratio will be affected4041. Indeed, in the present study, levels of acetate in the liver of the restricted group was lower than in the growth group.…”
Section: Discussionmentioning
confidence: 99%
“…Given the transforming influence of beekeeping on concepts of ownership, sedentism and exchange among East African foragers, the juxtaposition of images of bees with those of sheep in the uKhahlamba-Drakensberg should not be dismissed as an irrelevance in the context of the adoption of livestock-keeping by indigenous hunter-gatherer groups in southern Africa. A recent paper by Alves et al (2013) finds that the tail fat of the Damara sheep has a distinct chemical structure linked to a unique type of lipid metabolism. A similar marking of wild goods is described by Bleek (1928: 37) for the Naron (Nharo), among whom 'a man who finds an ostrich nest with one or two eggs, sticks his arrow in the ground close by as a sign of ownership'.…”
Section: Azania: Archaeological Research In Africa 17mentioning
confidence: 99%
“…This may be because of the role of the fat tail in maintaining the animal's condition, whereby ewes can mobilize fat depot when exposed to nutritional stress. 13 Moreover, the effects of nutrition on gonadotropin release are not very acute unless a severe nutritional restriction occurs in ruminants. 24 The slight decrease in dominant follicle and corpus luteum diameters observed in 50% restricted ewes was similar to that observed in llamas fed 40% and 70% …”
Section: Follicle Growth and Ovulation Ratementioning
confidence: 99%
“…Since fat depot able to be mobilized under nutritional stress. 13 Where, lipid was mobilized from the fat tails of sheep exposed to starvation in the form of free fatty acids. 14 The purpose of this study was to determine effects of feeding a half-maintenance diet for 30 days on growth dynamics and competence of preovulatory follicles, ovulation rate, body weight, metabolic changes, hormonal, and antioxidant markers in synchronized mature fat-tailed cyclic Barki, Rahmani, and Ossimi ewes.…”
Section: Introductionmentioning
confidence: 99%